Eksistensi Gender Perempuan Dalam Film Battle Of Sexes (Analisis Semiotika Roland Barthes) - Rifaldi, Riki (Komunika : Jurnal Ilmiah Komunikasi, 2024)
Woman gettting more proof that they can living their life with their own abilities. With the growth of mass media this time, woman existention become more exist. One of those following mass media that have huge influence was film. This film is also a film that bring up gender existention theme which woman fight for. This research purpose to know about gender existention using Roland Barthes semiotic analysis through denotation, conotation and myth indicator. This research using descriptive qualitative methode. Data collection technique is using observation and documentation to this film. Unit analysis using scenes which take from Battle of Sexes film. The result shown that gender existention is exist in this film. Denotation indicator shown that woman proof their existention in real. From conotation, through hidden messages also shown that woman has the equal existention with man. Myth in this film tell that man and woman has the same existention, either in personal life or in society. This film succeed to lead the audiens to realize that woman has no difference with man, they are equal being in this world.